The Role of Parental Attachment and Emotional Regulation on Schematic Investment in Appearance in Young Adults - da Costa Claro, Patrícia (2019)
The affective bonds that are established in childhood can have effects on the emotional development of young people. The secure attachment can potentiate the ability of emotional regulation, provide a more positive image of yourself and, therefore, adjusted investment behaviors in appearance. This study aims to analyze the role of parental attachment and the emotional regulation in the schematic investment in appearance. Self-report instruments were used on a sample that consisted of 948 young adults (18 and 30 years) of both genders. The study highlighted the significant role that the quality of parental attachment and emotional regulation take in developing an investment adjusted in appearance. The results showed the positive mediator effect of difficulties in emotional regulation between the inhibition of exploration and individuality mother and the self-evaluative salience.